The Influence Of Education, Competence, And Motivation On Human Resource Development At PT. JNE Express Main Branch In Medan - Mafazan Nuha Annisa; Kholilul Kholik (International Journal of Health, Economics, and Social Sciences (IJHESS), 2025)
This study aims to determine and analyze the influence of education, competence, and motivation on human resource (HR) development at PT. JNE Express Medan Main Branch. HR development is an important factor in increasing the effectiveness and efficiency of company operations, especially in the delivery service sector which is highly dependent on human performance. The independent variables in this study are education, competence, and motivation, while the dependent variable is HR development. The t-value of education is 1.834 > 1.684 (n-k 44- 4 = 40 at 0.05 / 5%) and is significant at 0.009 < 0.05, so education has a positive and significant effect on HR development. The t-value of competence is 1.747 > 1.684 (n-k 44- 4 = 40 at 0.05/ 5%) and significant 0.009 < 0.05, The t-value of education is 1.834 > 1.684 (n-k 44- 4 = 40 at 0.05/ 5%) and significant 0.009 < 0.05 The results of the study indicate that simultaneously education, competence, and motivation have a positive and significant effect on HR development. Partially, each variable also provides a significant contribution, where motivation has a dominant influence compared to other variables.